Alyson Economou: capstone - Economou, Alyson, artist (Colorado State University. Libraries, 2023)
The artist's statement: My design work is highly influenced by my art practice, especially through my use of color and my focus on how the eye moves across the page. When I'm able, I prefer to take on projects that help improve the world around me and give back to local communities.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design